2010
DOI: 10.1124/mol.110.066431
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs Regulate Hedgehog Signaling by Modulation of 7-Dehydrocholesterol Reductase Levels

Abstract: Recently we identified GANT61, a small-molecule antagonist of Gli transcription factors, which are the final effectors of the mammalian Hedgehog (HH) signaling pathway. Here we describe a diamine substructure of GANT61 that carries the biological activity and show that this part of the molecule is structurally related to trans-1,4-bis(2-chlorobenzaminomethyl)cyclohexane dihydrochloride (AY9944), an inhibitor of the enzymatic activity and transcriptional inducer of 7-dehydrocholesterol-reductase (Dhcr7, EC 1.3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 32 publications
(43 reference statements)
2
61
0
Order By: Relevance
“…Schizophrenic patients are on a wide variety of medications, including anticonvulsants and antipsychotic drugs [46,47]. Our findings showed no significant association between those taking antipsychotics and vitamin D level, in line with other studies that showed no effect of antipsychotics on vitamin D level [1,48,49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Schizophrenic patients are on a wide variety of medications, including anticonvulsants and antipsychotic drugs [46,47]. Our findings showed no significant association between those taking antipsychotics and vitamin D level, in line with other studies that showed no effect of antipsychotics on vitamin D level [1,48,49].…”
Section: Discussionsupporting
confidence: 89%
“…It is hypothesized that anti psychotics would cause hypogonadism and might predispose the patient to a higher risk of osteoporosis [50] however, it is not known whether there are direct effects of this class of medications on vitamin D status [1]. Some anticonvulsant medications might increase the rate of vitamin D removal from the body via the liver [51] by enhancing the catabolism of vitamin D [47], thus, putting the patient at risk of low vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%
“…This was not expected because in the adult tissues and cells, transcriptional regulation of Dhcr7 is in line with the cholesterol feedback loop and transcription factors of the sterol regulatory element binding transcription protein family. Dhcr7 mRNA is inducible under sterol starvation or when treated with cholesterol synthesis inhibitors in the liver (34) and brain (35). Proteomic studies confirmed the increased expression of cholesterol synthesis enzymes in brains of the Dhcr7 null mice (36).…”
Section: Discussionmentioning
confidence: 94%
“…It is worth noting that newer HDAC6 inhibitors are able to penetrate the blood-brain barrier and can therefore be tested under more physiologic conditions in autochthonous medulloblastoma mouse models in the future (63). Interestingly, these newer HDAC6 inhibitors have been shown to possess antidepressive characteristics, a phenomenon that we have linked to Hh inhibition before (64).…”
Section: Discussionmentioning
confidence: 99%